The Implementation of Contextual Teaching and Learning in Student Character Building - Azizah, Nur; Permanasari, Pradnya; Jamal, Mujtaba (Faculty of Humanities, Universitas Jenderal Soedirman, 2024)
The aim of education is not only to improve students' academic performance but also to develop their character. In line with these aims, the author conducted research to describe the teaching strategies of English teachers in building students' character through character education and to examine the effect of contextual teaching and learning on students' character development in the eleventh-grade students of SMK Islam Bojong during the academic year 2021-2022. The author used descriptive qualitative research with purposeful sampling, involving 28 students as the study population. Data were collected using interviews and observation sheets. The data were analyzed using a data triangulation technique. The results showed that contextual teaching and learning can effectively enhance students' character. Contextual teaching and learning also positively impact character building in the eleventh-grade students of SMK Islam Bojong. The author concludes that the contextual teaching and learning strategy is beneficial for integrating character-building into the learning process. It provides students with a valuable learning experience, emphasizing that education is not just about achieving high scores but also about developing good behavior.